"Tinjauan Terhadap Perjanjian Baku pada Akad Pembiayaan Syariah Menurut Hukum Islam (Analisis Terhadap Akad No. 007/WKL/UMS/0117/9310/IV/2013 BRI Syariah)" - zulkifli Zulkifli; Musrifah; Madona Khairunisa (Jurnal Hukum Islam, 2018)
Some literature suggests that Islamic banking, particularly in terms of financing agreement, always employs standard contracts. The contracts are agreement to the clauses that have already been established unilaterally by one party possessing a stronger position; the party is the bank. Consequently, customers basically cannot negotiate for the content of the contracts. It is worth mentioning that the unilateral decision is contrary to the Surah An-Nisa Verse 29 asserting that trade should be based on a consensus between two parties. The research findings reveal that the standard contracts can be justified in the view of Islam since it is a ‘mubah’ case that is not prohibited by the Qur’an in relation to ‘qath’y’, especially the ‘maqasid’ (purposes) of the standard contracts for the sake of ease and acceleration in the contracts. For instance, the contract No. 007/WKL/UMS/0117/9310/IV/2013 BRI Syariah is actually in accordance with sharia principles. This contract discusses the time for purchasing goods dealing with ‘murabahah’ (cost plus profit) financing, but the implementation of the contract is deemed inappropriate according to the sharia principles.